2020
DOI: 10.1002/phar.2362
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interaction Between Febuxostat and Thiopurine Antimetabolites: A Review of the FDA Adverse Event Reporting System and Medical Literature

Abstract: BACKGROUND There is a known drug interaction (DI) between xanthine oxidase (XO) inhibitors and the thiopurine immunosuppressants, azathioprine (AZA) and mercaptopurine (6-MP). Xanthine oxidase inhibition increases concentrations of AZA and 6-MP active metabolites, possibly resulting in myelosuppression. When allopurinol is used with AZA or 6-MP, dose reduction of AZA or 6-MP is recommended. Febuxostat is a newer XO inhibitor approved for the treatment of gout. OBJECTIVE To determine the clinical impact of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The blood concentration of AZA is elevated when administrated with xanthine oxidase inhibitor, which is a metabolic enzyme of 6‐MP, and the adverse effects are exacerbated by the competitive drug interaction. 19 , 20 Hence, a potential risk with the co‐administration of these two drugs has been reported 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…The blood concentration of AZA is elevated when administrated with xanthine oxidase inhibitor, which is a metabolic enzyme of 6‐MP, and the adverse effects are exacerbated by the competitive drug interaction. 19 , 20 Hence, a potential risk with the co‐administration of these two drugs has been reported 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…131 Current febuxostat labeling contraindicates concomitant administration of febuxostat with either azathioprine or 6-mercaptopurine. 132 Topiroxostat is a novel, nonpurine, selective xanthine oxidase inhibitor approved in Japan that has demonstrated a strong effect against hyperuricemia. Several reports suggest an important protective effect against progression of kidney disease and proteinuria.…”
Section: Treatmentmentioning
confidence: 99%
“…While allopurinol only leads to the inhibition of reduced forms of XO, febuxostat, a newer selective non-purine-based XO inhibitor, inhibits both oxidized and reduced forms and seems to have a greater potency to inhibit XO [41,42]. It seems likely that co-administration of XO inhibitors and thiopurines causes a similar metabolic shift of thiopurine metabolism, and a case series demonstrated that concomitant use is indeed associated with TGNinduced myelosuppressive adverse events [42]. Sulfasalazine and other 5-aminosalicylic acid (5-ASA) derivates, used in gram doses to treat IBD, were shown to be potent in vitro inhibitors of recombinant human TPMT [43][44][45].…”
Section: Drug-induced Effects On Thiopurine Metabolismmentioning
confidence: 99%
“…Although the biological mechanism of this switch in preferential metabolism is not completely elucidated, it is suggested that TPMT is directly inhibited because of an increase in thioxanthine, which is a consequence of the inhibition of xanthine dehydrogenase by oxypurinol, the active metabolite of allopurinol [ 40 ]. While allopurinol only leads to the inhibition of reduced forms of XO, febuxostat, a newer selective non-purine-based XO inhibitor, inhibits both oxidized and reduced forms and seems to have a greater potency to inhibit XO [ 41 , 42 ]. It seems likely that co-administration of XO inhibitors and thiopurines causes a similar metabolic shift of thiopurine metabolism, and a case series demonstrated that concomitant use is indeed associated with TGN-induced myelosuppressive adverse events [ 42 ].…”
Section: Pharmacokineticsmentioning
confidence: 99%